110 Myocardial tissue characterisation in heart failure patients with and without left bundle branch block. (17th July 2020) - Wahab, Ali; Brown, Louise; Saunderson, Christopher; Das, Arka; Craven, Thomas; Chowdhary, Amrit; Jex, Nicholas; Levelt, Eylem; Dall'Armellina, Erica; Xue, Hui; Kellman, Peter; Greenwood, John; et al.
Abstract : Background: Heart failure patients with left bundle branch (LBBB) have worse outcomes than their counterparts with narrow QRS across the range of ejection fraction. We aimed to investigate whether patients with LBBB have different patterns of fibrosis and perfusion. Method: We prospectively recruited 177 patients with new diagnosis of left ventricular systolic dysfunction (LVSD) of unknown aetiology. Exclusion criteria included presence of angina symptoms or previous known ischaemic heart disease. Surface 12 lead electrocardiogram was reviewed in all patients to diagnose LBBB. All patients underwent cardiovascular magnetic resonance (CMR) on a Siemens 3.0T Prisma system with a protocol that included cine imaging for volumetric analysis, pre and post contrast T1 mapping and free breathing quantitative inline perfusion mapping. Pharmacological stress was achieved via adenosine administration at 140mcg/kg/min increased up to a maximum of 210mcg/kg/min as required to achieve symptoms and/or haemodynamic response. Segments with fibrosis detected on late gadolinium enhancement imaging or inducible ischaemia were excluded from analysis. Global measures of native T1, extracellular volume fraction (ECV), stress and rest myocardial blood flow (MBF) and myocardial perfusion reserve (MPR) were calculated. Results: There was no difference in age, gender of functional class between those with (n=65) and without LBBB (n=112). There was no difference between those with and without LBBB in prevalence of ischaemic fibrosis (8(12%) vs 23(21%), p=0.17), non-ischaemic fibrosis (22(34%) vs 36 (32%), p= 0.82) or inducible ischaemia (3(5%) vs 9 (8%), p=0.38). Patients with LBBB had greater LVEDVi (118ml/m2 vs 102ml/m2 P=0.002) and LV mass index (72g/m2 vs 64g/m2 P=0.001). There was no difference in LVEF, RVEDVi or RVEF. There was no difference in native T1, ECV, stress MPF, rest MBF or MPR. Conclusion: In presenting patients with heart failure of unknown aetiology LBBB was only associated with increased LVEDVi and LV mass index. LBBB was not associated with a difference in MPR, focal or diffuse fibrosis. This suggests that the adverse prognosis associated with LBBB is not mediated by differences in tissue characteristics. Further analysis is needed to establish whether patients with LBBB have differences in extent and location of fibrosis. Conflict of Interest: None